Closure or Connection? Healing from Trauma in Richard Van Camp’s The Lesser Blessed - Vedal, Lauren (Studies in Canadian Literature, 2013)
Richard Van Camp’s 1996 novel The Lesser Blessed contributes to a literature that testifies to the effects of Canadian residential schools on First Nations people. The narrator, Larry Sole, is the son of two residential school survivors. Sexually abused by his father, Larry relives his (and his parents’) traumatic past in classically psychoanalytic terms: through a fragmented narrative, the return of the repressed, and acting out. From the perspective of individual recovery, Van Camp details Larry’s psychological process of becoming whole. However, there is a broader, systemic rupture that remains unresolved — that of Canada’s historical violence toward as well as continuing unjust treatment of First Nations peoples. The novel portrays a tension between individual recovery and national healing that can be understood in terms of dominant and Indigenous views of reconciliation. Reading The Lesser Blessed through the lens of reconciliation reveals a dynamic and double-edged vision of healing, through which we can understand Canada-First Nations relations as ongoing, ambiguous negotiations. The double-edged story relies on an enduring relationship between past injury and the present as well as a relationship between parties whose identities and attitudes are inherently tied to that past.